Macedonian dairy farmers and their choice of buyers - Krstevska, Ana (2008)
The dairy farming in the Republic of Macedonia operates under high uncertainties, where the not well regulated institutional environment creates unsuccessful governance structures. The study aims to indentify the transaction cost factors and household characteristics that influence the farmers' choice of milk marketing channel. The prime focus is to present a theoretically structured framework of the contractual arrangements between milk producers and dairy processors based on Transaction Costs Economics' predictions.